Bifurcation Type and Larger Low Shear Area Are Associated with Rupture Status of Very Small Intracranial Aneurysms - Zhang, Yisen; Tian, Zhongbin; Jing, Linkai; Zhang, Ying; Liu, Jian; Yang, Xinjian (Frontiers in Neurology, 2016)
Background: Characterization of the risk factors for rupture of very small intracranial aneurysm (VSIA, ≤3 mm) is clinically valuable, since VSIAs are implicated in subarachnoid hemorrhage. The aim of this study was to identify morphological and hemodynamic parameters that independently characterize the rupture status of VSIAs. Methods: We conducted a retrospective study of consecutive VSIAs between September 2010 and February 2014 in our institute. A series of morphologic and hemodynamic parameters were evaluated using computational fluid dynamics, based on patient-specific three-dimensional geometrical models. Results: We identified 186 patients with 206 VSIAs (73 ruptured, 133 unruptured). Univariable logistic regression analysis showed that bifurcation type, parent artery diameter, size ratio, time-averaged wall shear stress (WSS), maximum WSS, minimum WSS, and low shear area (LSA) were related to rupture status. Bifurcation type and larger LSA were independently associated with rupture status in multivariable logistic regression (p=0.002 and p=0.003, respectively). Conclusion: Bifurcation type and larger LSA were independently associated with VSIA rupture status. Further studies are needed prospectively on patient-derived geometries prior to rupturing based on large multi-population data to confirm the present findings.